2010
DOI: 10.1080/02626661003780458
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation from shallow groundwater in closed basins in the ChileanAltiplano

Abstract: The hydrological cycle in arid and semi-arid climates is highly controlled by evaporation. The correct quantification of this process is essential for improving the accuracy of water balance estimates, especially in closed basins. The objective of this paper is to characterize evaporation rates from shallow groundwater using the chamber approach in six closed basins in the Altiplano of northern Chile. Measurements were made at 49 locations with water-table depths ranging from 0.09 m to 3.3 m. Estimated daily e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 22 publications
2
40
1
Order By: Relevance
“…Therefore, a larger diel range in baseflow during periods of higher water table is consistent with a conceptual model that implies a larger impact of ET when the groundwater table is closer to the ground surface. As indicated by Johnson et al (), the highest rates of ET are found where groundwater tables are shallow and soils have a coarse texture. Finally, the absence of losing reaches rules out the likelihood that temperature‐mediated increases in daytime infiltration (Constantz, ) contributed to the diel baseflow signal.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a larger diel range in baseflow during periods of higher water table is consistent with a conceptual model that implies a larger impact of ET when the groundwater table is closer to the ground surface. As indicated by Johnson et al (), the highest rates of ET are found where groundwater tables are shallow and soils have a coarse texture. Finally, the absence of losing reaches rules out the likelihood that temperature‐mediated increases in daytime infiltration (Constantz, ) contributed to the diel baseflow signal.…”
Section: Discussionmentioning
confidence: 99%
“…In closed Altiplano basins such as those encountered in arid and hyper arid basins in the northern Chile, evaporation is the main source of aquifer depletion, and thus its study is crucial for water resources management. Understanding evaporation is also important for the study of sensitive soil systems such as wetlands (de la Fuente and Niño, ; Johnson et al, ). Nonetheless, understanding the evaporation processes in these environments is complex because evaporation occurs under non‐isothermal conditions, where water can be mobilized as liquid water or water vapour (Nassar and Horton, ; Grifoll et al, ; Hernández‐López et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the most depleted isotopic values in groundwater would represent recharge at higher altitudes. Conversely, water retained in the surface and shallow aquifers are significantly affected by evaporation [10,30]. As a consequence, the most enriched isotopic compositions are expected in samples of the aforementioned sites.…”
Section: Isotopic Compositions In Surface Water and Groundwatermentioning
confidence: 99%